2014
DOI: 10.3109/15563650.2014.932365
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury associated with smoking synthetic cannabinoid

Abstract: Whether caused by direct toxicity, genetic predisposition, or an as-yet unidentified nephrotoxin, this association between synthetic cannabinoid exposure and acute kidney injury reinforces the need for vigilance to detect new toxicologic syndromes associated with emerging drugs of abuse. Liquid chromatography and time-of-flight mass spectrometry are useful tools in determining the active ingredients in these evolving products and evaluating them for toxic contaminants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(61 citation statements)
references
References 48 publications
3
56
0
2
Order By: Relevance
“…Other explanations for rhabdomyolysis include contamination of the recreational product used by the patient and rhabdomyolysis secondary to the hyperemesis-induced electrolyte abnormalities. Importantly, reports in the literature directly implicate synthetic cannabinoids as a cause of renal damage [4,5]. In the absence of a kidney biopsy and given the negative urine drug screen, the synthetic cannabinoid product ingested by the patient is the only identifiable cause of the present illness.…”
mentioning
confidence: 99%
“…Other explanations for rhabdomyolysis include contamination of the recreational product used by the patient and rhabdomyolysis secondary to the hyperemesis-induced electrolyte abnormalities. Importantly, reports in the literature directly implicate synthetic cannabinoids as a cause of renal damage [4,5]. In the absence of a kidney biopsy and given the negative urine drug screen, the synthetic cannabinoid product ingested by the patient is the only identifiable cause of the present illness.…”
mentioning
confidence: 99%
“…In addition, the CDC reported a stark increase of calls regarding effects from SC use by 229% in 2015 from the same January-May period in 2014 [2]. Although it is apparent the prevalence of SC use is on the rise, Buser et al found that young adults and adolescents appear to be unaware of the health risks associated with synthetic cannabinoids [5].…”
Section: Discussionmentioning
confidence: 99%
“…A further case report regarding a 26 year old male admitted to hospital with AKI and use of "Mr Happy" has been published [97]. He experienced abdominal pain, nausea, vomiting and low back pain.…”
Section: Case Reports/series With No Analytical Confirmation Of Scra(s)mentioning
confidence: 97%